Plasmodium falciparum: a paradigm for alternative folate biosynthesis in diverse microorganisms? - Hyde, J; Dittrich, S; Wang, P; Sims, P; de Crécy-Lagard, V; Hanson, A (2008)
Folates have a key role in metabolism, and the folate-dependent generation of DNA precursors in the form of deoxythymidine 5'-phosphate is particularly important for the replication of malaria parasites. Although Plasmodium falciparum can synthesize folate derivatives de novo, a long-standing mystery has been the apparent absence of a key enzyme, dihydroneopterin aldolase, in the classical folate biosynthetic pathway of this organism. The discovery that a different enzyme, pyruvoyltetrahydropterin synthase, can produce the necessary substrate for the subsequent step in folate synthesis raises the question of whether this solution is unique to P. falciparum. Bioinformatic analyses suggest otherwise and indicate that an alternative route to folate could be widespread among diverse microorganisms and could be a target for novel drugs.